Japan : Background Papers. (IMF Staff Country Reports; Country Report ;, 1995)
This Background Papers on Japan analyzes the recent movements of the yen from a long-term perspective. It reviews the movements in the real value of the yen during the post-war period. The paper highlights that movements in the Consumer Price Index (CPI)- and WPI-based real exchange rate are shown to be characterized by transitory deviations around stable time trends. The paper discusses potential explanations for the secular real appreciation of the yen. The paper also examines the tax reform issues in Japan.